Phenol influence on winter wheat grain quality - Баган, А. В. (Scientific Progress & Innovations, 2012)
118 soft winter wheat varieties of different geographical origin are analyzed by grain quality indices. The varieties are divided into groups depending on grain coloration with the help of phenolic test. The level of manifestation of grain quality indices of winter wheat varieties according to groups of phenolic test is established. The 5th group varieties with better grain quality are selected. It is established that winter wheat varieties Levada, Zolotokolosa, Remeslivna, Harus are valuable sources for getting selecting material of high quality.